Bidrag til Vendelbo Stifts Kirkehistorie siden Reformationen - Rørdam, H. F. (Kirkehistoriske Samlinger, 1882)
Hr. Peder Thomesen Dr. theol. Oluf Chrysostomus Mester Lavrits Nielsen Riber Mester Jørgen Mortensen Boringholm Mester Jakob Jensen Holm Mester Christen Hansen (Riber) Dr. theol. Anders Andersen (Ringkjøbing)